Membrane cholesterol access into a G-protein-coupled receptor - Guixà-González, Ramon; Albasanz, José L; Rodriguez-Espigares, Ismael; Pastor, Manuel; Sanz, Ferran; Martí-Solano, Maria; Manna, Moutusi; Martinez-Seara, Hector; Hildebrand, Peter W; Martín, Mairena; Selent, Jana (Nature communications, 2017)
Cholesterol is a key component of cell membranes with a proven modulatory role on the function and ligand-binding properties of G-protein-coupled receptors (GPCRs). Crystal structures of prototypical GPCRs such as the adenosine A2A receptor (A2AR) have confirmed that cholesterol finds stable binding sites at the receptor surface suggesting an allosteric role of this lipid. Here we combine experimental and computational approaches to show that cholesterol can spontaneously enter the A2AR-binding pocket from the membrane milieu using the same portal gate previously suggested for opsin ligands. We confirm the presence of cholesterol inside the receptor by chemical modification of the A2AR interior in a biotinylation assay. Overall, we show that cholesterol's impact on A2AR-binding affinity goes beyond pure allosteric modulation and unveils a new interaction mode between cholesterol and the A2AR that could potentially apply to other GPCRs.
Keywords: buněčná membrána; Receptors, G-Protein-Coupled; Cholesterol; cholesterol; Protein Binding; Receptor, Adenosine A2A; receptor adenosinový A2A; krysa rodu Rattus; vazebná místa; proteinové domény; zvířata; Binding Sites; simulace molekulární dynamiky; Molecular Dynamics Simulation; kompetitivní vazba; vazba proteinů; Protein Domains; Binding, Competitive; nádorové buněčné linie; Rats; Animals; Cell Line, Tumor; Cell Membrane; receptory spřažené s G-proteiny